2019
DOI: 10.1088/1755-1315/341/1/012169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metallic nanoparticles on exchange of chemical elements in broiler chickens

Abstract: We studied the effect of chromium (III) oxide nanoparticles of various dosages on the elemental status of the organism. Experimental studies were conducted using 150 heads of broiler chickens "Arbor Aykres". The control groups of birds received the main ration, and the experimental groups received chromium (III) oxide nanoparticles in doses of 50; 100; 200 and 400 μg/kg feed. It was noted that with the introduction of chromium (III) oxide nanoparticles into the diet, an increase in the content of Ca, Zn, Cr, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…For this reason, researchers are increasingly interested in complexes of Cr with amino acids, such as methionine or glycine [ 18 , 19 ] as well as inorganic chromium nanoparticles [ 20 ]. It is believed that the lack of electric charge and the small size of chromium nanoparticles can modify their properties in a living organism and improve bioavailability relative to their standard counterparts [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, researchers are increasingly interested in complexes of Cr with amino acids, such as methionine or glycine [ 18 , 19 ] as well as inorganic chromium nanoparticles [ 20 ]. It is believed that the lack of electric charge and the small size of chromium nanoparticles can modify their properties in a living organism and improve bioavailability relative to their standard counterparts [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the addition of Cr to the diet of chickens increased the concentration of Ca and Fe and decreased the concentration of Cu and Zn in their blood plasma. Similarly, Gubajdullina et al [41] found that supplementation of a chicken's diet with chromium (III) oxide nanoparticles at 50-400 µg/kg caused an increase in Fe and Ca content, while a decrease in Zn and Cu content in the body of birds. Iron is a cofactor for tyrosine hydroxylase and tryptophan hydroxylase, enzymes that are responsible for dopamine and serotonin synthesis, respectively [42], while magnesium affects norepinephrine level [43].…”
Section: Discussionmentioning
confidence: 92%
“…A promising approach may be the use of nanoforms of microelements [7,8] which have unique properties that allow them to be competitive sources of chemical elements for mineral additives [9,10]. A number of studies confirmes the high efficiency of metal nanoforms compared to inorganic salts and other sources [11][12][13].…”
Section: The Effectiveness Of Various Forms Of Zn As Stimulators Of T...mentioning
confidence: 99%